Beyond Intrinsic Drives: The Synergistic Role of Work Environment in Enhancing Employee Performance in Higher Education (International Journal of Economics and Management Research, 2026)
This study examines employee performance in higher education, focusing on the role of work motivation and the work environment at STISIP Bina Putera Banjar. The research is driven by the gap between stakeholder expectations and institutional performance, as well as limited empirical evidence on the combined effects of motivational and environmental factors in Indonesian private higher education. This study aims to analyze the individual and simultaneous influence of these variables on employee performance. A quantitative approach with a census method was applied to 65 employees. Data were collected through validated Likert-scale questionnaires and analyzed using descriptive statistics and multiple regression. The results show that work motivation has a strong and significant effect (r = 0.630; 39.7%), while the work environment has a weaker but significant effect (r = 0.227; 5.2%). Together, both variables have a substantial combined influence (R = 0.790), explaining 62.4% of performance variance. In conclusion, employee performance is shaped by both intrinsic and contextual factors, with motivation as the dominant driver. This study highlights their synergistic role and suggests integrated human resource strategies to enhance sustainable performance.